Optimization and characterization of biosurfactant produced by indigenous Brevibacillus borstelensis isolated from a low permeability reservoir for application in MEOR. Issue 4 (12th January 2022) - Dong, Hao; Zheng, Anying; He, Yanlong; Wang, Xiaotong; Li, Yang; Yu, Gaoming; Gu, Yongan; Banat, I. M.; Sun, Shanshan; She, Yuehui; Zhang, Fan
Abstract : Biosurfactants are expected to be a key factor for microbial enhanced oil recovery (MEOR). Abstract : Biosurfactants are expected to be a key factor for microbial enhanced oil recovery (MEOR). In this study, we described the novel biosurfactant-producing strain Brevibacillus borstelensis YZ-2 isolated from a low permeability oil reservoir. We purified and characterized the biosurfactants produced by this YZ-2 strain via thin-layer chromatography and MALDI-TOF-MS, revealing them to be fengycins. We additionally used a Box–Behnken design approach to optimize fermentation conditions in order to maximize the biosurfactants production. Core flooding experiments showed that biosurfactants produced by YZ-2 can significantly enhance crude oil recovery. Micro-model tests showed that emulsification and IFT reduction was the main EOR mechanism of the YZ biosurfactant in the oil wet model. In summary, these findings highlight the potential of Brevibacillus borstelensis YZ-2 and its metabolites for MEOR.